Knockdown of ATF3 suppresses the progression of ischemic stroke through inhibiting ferroptosis - Ye, Jin; Zhang, Fan; Li, Bin; Liu, Qing; Zeng, Guoyong (Frontiers in Molecular Neuroscience, 2023)
Objective Current therapies towards ischemic stroke (IS) are still not satisfied, and alternative strategies targeting ferroptosis may be another choice. The purpose of this study is to screen potential ferroptosis-related genes involving in IS. Methods A rat model of IS was established via middle cerebral artery occlusion. Differentially expressed genes (DEGs) were screened from the model rats through transcriptional sequencing. Among the isolated DEGs, the expression of several attractive DEGs relating with ischemic injury was confirmed by qRT-PCR. Then, ATF3 relating with both IS and ferroptosis was selected a candidate gene for functional assays. After knockdown of ATF3 in the model rats, the infarction, histopathology, apoptosis, and ferroptosis in brain tissues were evaluated. Results IS model was successfully established in rats, exhibiting the emergence of infarction area, histopathological injury, and enhanced cell apoptosis. Total 699 up-regulated DEGs and 461 down-regulated DEGs were screened from the model rats. qRT-PCR verified the up-regulation of Hspa1b, Tfpi2, Ptx3, and Atf3, and the down-regulation of Smyd1 and Tacr2 in the Model group compared with those in the Sham group. It is noteworthy that knockdown of ATF3 decreased the infarction area, relieved histopathological injury, weakened apoptosis, and inhibited ferroptosis in the model rats. Conclusion Several candidate genes in relation with IS were revealed. More importantly, knockdown of ATF3 may relieve IS through inhibiting ferroptosis.